Results of an early access treatment protocol of daratumumab in United States patients with relapsed or refractory multiple myeloma. Issue 22 (5th November 2018) - Chari, Ajai; Lonial, Sagar; Mark, Tomer M.; Krishnan, Amrita Y.; Stockerl‐Goldstein, Keith E.; Usmani, Saad Z.; Londhe, Anil; Etheredge, Delores; Fleming, Sarah; Liu, Baolian; Ukropec, Jon; Lin, Thomas S.; et al.
Abstract: Background: Daratumumab is a human CD38‐directed monoclonal antibody indicated for the treatment of relapsed and refractory multiple myeloma (MM). Methods: A multicenter, open‐label treatment protocol provided early access to daratumumab for patients who had progressive MM after they received ≥3 prior lines of therapy that included a proteasome inhibitor and an immunomodulatory agent or if they were refractory to both a proteasome inhibitor and an immunomodulatory agent. Patients received daratumumab 16 mg/kg weekly for 8 weeks, every other week for 16 weeks, and monthly until they developed disease progression, unacceptable toxicity, or 60 days after the drug gained US approval. Treatment‐emergent grade ≥3 adverse events (AEs), serious AEs, and AEs of special interest were collected. Results: Three hundred forty‐eight patients were enrolled at 39 US sites between June and December 2015. Patients received study therapy for a median of 1.9 months (range, 0.03‐6.0 months). Fifty‐two percent of patients transitioned to commercially‐available daratumumab and 37% discontinued because of progressive disease. Grade ≥3 AEs occurred in 50% of patients, including thrombocytopenia (15%) and anemia (14%). Serious AEs occurred in 35% of patients (12% were drug‐related), including infections (11%). Infusion reactions occurred in 56%, 2%, and 2% of patients during the first, second, and all subsequent infusions, respectively; respiratory symptoms (cough, dyspnea, throat irritation, nasal congestion) were common. The infusion reaction rate for the first infusion was 38% in 50 patients at 2 sites who received montelukast as premedication for their first infusion and 59% in patients who did not receive montelukast. Conclusions: The current findings are consistent with previously reported trials and confirm the safety profile of daratumumab in heavily pretreated US patients who have relapsed or refractory MM. Cancer 2018;124:000‐000. Abstract : An early access treatment protocol confirms the safety profile of daratumumab in patients with relapsed or refractory myeloma. Findings from 2 study sites (60 patients) that used montelukast premedication indicate reduced infusion reactions and infusion time associated with the first dose of daratumumab.